Preparation and characterization of magnesium aluminate (MgAl2O4) spinel ceramic foams via direct foam-gelcasting. Issue 1 (January 2020) - Qiao, Jian; Wen, Yubin
Abstract: Lightweight MgAl2 O4 spinel ceramic foams with high mechanical strength and good dielectric properties were prepared with a direct foam-gelcasting method using MgAl2 O4 and TiO2 (rutile phase, as sintering aid) powders. The effects of calcination temperature and foam volume on bulk density, apparent porosity, and on the mechanical and dielectric properties of the ceramic foams were investigated. Tailored porosity (75.14–82.46%), pore size (10–200 μm), dielectric constant (1.66–2.05), and compressive strength (4.0–14.3 MPa), were obtained based on the change of the foam volume in the foamed slurries, and the calcination temperature of porous ceramics. The compressive strength and dielectric constant of the as-manufactured spinel foam with a porosity of ~75.14% was as high as 14.3 MPa and 2.05, respectively. The spinel ceramic foam which had a porosity of 81.84% was prepared with a foam volume of 350 mL and a sintering temperature of 1500 °C, and exhibited heterogeneous pore structures, whereby large and open spherical cells involved in small circular windows on the internal walls with a mean pore size of ~66.26 μm and a grain size of ~8 μm. The experimental dielectric constant matches well with that calculated by the modified Bruggeman model. The dependence of the mechanical strength on the relative density can be represented by the Gibson and Ashby model. The fitted index values of the power relationship were 3.504 and 3.533, compared to the theoretical value of 1.5. The ceramic foam can potentially become a new type of electromagnetic wave-transmitting radome material due to its low dielectric constant (1.66–2.05) and dielectric loss (0.0026–0.006) values.